2013
DOI: 10.1002/cjce.21818
|View full text |Cite
|
Sign up to set email alerts
|

Understanding of no‐load power in low consistency refiners

Abstract: Low consistency refining is primary means of improving the paper quality by imparting energy to fibres through repeated fibre–bar interactions. Useful part of the energy modifies the morphology of fibres and the remaining, no‐load power, overcomes the hydraulic, pumping and mechanical losses in the refiner. In this study, effect of consistency, operational and plate design parameters on no‐load power was experimentally determined on two pilot scale refiners with different diameters. Obtained data were used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Recently, authors experimentally showed that the measured power as a function of gap size for an LC refiner, when there is no refining action on fibres, is similar when running a refiner with either low consistency mechanical pulp or water . Thus, in this study, water has been considered as the fluid between two corrugated walls with the density of 998.3thinmathspacenormalkg/m3 and viscosity of 0.001003 kg/m.s.…”
Section: Computational Frameworkmentioning
confidence: 94%
See 1 more Smart Citation
“…Recently, authors experimentally showed that the measured power as a function of gap size for an LC refiner, when there is no refining action on fibres, is similar when running a refiner with either low consistency mechanical pulp or water . Thus, in this study, water has been considered as the fluid between two corrugated walls with the density of 998.3thinmathspacenormalkg/m3 and viscosity of 0.001003 kg/m.s.…”
Section: Computational Frameworkmentioning
confidence: 94%
“…In the LC refiner, fibres experience the effect of refining only in the range of very small gap sizes while consuming high amount of energy. As gap slowly increases, the effect of the refiner on fibres diminishes, the power consumption decreases, and ultimately, approaches a minimum constant value at wide gaps …”
Section: Introductionmentioning
confidence: 99%
“…The LC refining process is usually characterized by the refining intensity and specific refining energy. Most refining intensities, such as the specific edge load (SEL) [5] , specific surface load (SSL) [6] , and net normal force or tangential force per bar crossing zone [7] , have been proposed and calculated based on the net power obtained by subtracting the no-load power from the total power [8][9] . This indicates that the accurate measurement or calculation of net power is important for controlling LC refining.…”
Section: Introductionmentioning
confidence: 99%
“…Refining efficiency, defined as the ratio of net power to total power [10] , can be improved by increasing the net power or reducing the no-load power, which is approximately in the range of 20%-50% of the total power in LC refining [11] , and is related to refining devices, plate size, and other control or bar parameters [12] . The definition, calculation, and measurement methods for the no-load power have been summarized in previous studies [9,12] .…”
Section: Introductionmentioning
confidence: 99%
“…The no-load power of disc refiner in LC refining increase with the increasing of the plate diameter (Rajabi Nasab et al, 2013;Banks, 1967), and the net power is proportional to the rotation speed of the plates, while the no-load power is proportional to the cube of it (Ragnar, 1970). The pulp properties, such as pulp consistency, pulp type, etc., would affect the power consumption and the impact performance on pulp in the LC refining.…”
Section: Introductionmentioning
confidence: 99%